Modeling and analysis of an ankle-foot orthosis (AFO) using multibody methodologies - Ferreira, Philippe (2013)
Biomechanics is the scientific domain which deals with the study of biological systems, such as the human body, using physical concepts and mechanical engineering methodologies. It allows the development of new medical devices and provides a quantitative analysis of the subject being studied. In the present work, the effect of an ankle foot orthosis (AFO) was studied on a healthy male subject. For this purpose, a biomechanical multibody 2D- model was developed in code MOBILE. The model was made of 9 rigid bodies connected by 9 frictionless hinged joints. Three additional degrees-of- freedom (DOFs) were added so the model can move freely in the plane. Kinematic data acquired in a gait lab were used as time functions to drive the joints and a foot model was designed based on three Hunt-Crossley’s spheres-plane contact model. The measured ankle kinematics was successfully reproduced using forward dynamics principles, for the stance phase period. In a first approach, barefoot kinematics was reproduced to define the foot model properties by adjusting manually the foot parameters and fitting the ankle angle. The ankle moment obtained in the gait lab was used to power the ankle joint. Then, the ankle-foot orthosis was added as a linear torsional spring element acting at the ankle joint and the moment powering the ankle joint was diminished. A manual optimization process was performed in order to fit the ankle ankle and it was concluded that the AFO reduces the muscle moment developed at the ankle in 15% and it can be simulated as a spring with k = 50 N.m/rad.